HMGB1-TLR4-IL23-IL17A axis promotes paraquat-induced acute lung injury by mediating neutrophil infiltration in mice - Bailing Yan (Nature Portfolio, 2017)
Abstract Paraquat is a poisoning herbicide that primarily targets lung, leading to severe acute lung injury characterized by extensive neutrophil infiltration. However, the mechanisms underlying the neutrophil infiltration is not clear. In this study, we demonstrated the significance of the signaling cascade from high-mobility group box 1 (HMGB1), to Toll-like receptor 4 (TLR4), interleukin-23 (IL-23), and lastly to IL-17A during the paraquat-induced neutrophil infiltration and the subsequent lung injury in mice. Paraquat challenge significantly elevated serum levels of IL-17A and IL-23, the percentage of IL-17A-producing γδT cells in the lung, and the level of HMGB1 in bronchoalveolar lavage fluid. Reducing IL-17A production using an anti-γδT antibody, targeting IL-23 with the neutralizing antibody against IL-23p19, and blocking HMGB1 signaling by using glycyrrhizin or TLR4−/− mice all dramatically inhibited the infiltration of neutrophils and attenuated lung injury. These novel findings not only reveal the critical role of HMGB1-TLR4-IL-23-IL-17A axis in the pathogenesis of paraquat-induced acute lung injury, but also provide promising therapeutic targets for treating paraquat poisoning.